A remote sensing-based evaluation of an ungauged drainage basin in Southwestern Nigeria - Adewole, Adedayo Oreoluwa; Eludoyin, Adebayo O (Taylor & Francis, 2020)
INTERNATIONAL JOURNAL OF RIVER BASIN MANAGEMENT, Issue no:2019, Pg:1-13.